Strain difference in transgene-induced tumorigenesis and suppressive effect of ionizing radiation - Dutta, Bibek (J Radiat Res, 2020)
Transgenic expression in medaka of the Xiphophorus oncogene xmrk, under a pigment cell specific mitf promoter, induces hyperpigmentation and pigment cell tumors. In this study, we crossed the Hd-rR and HNI inbred strains because complete genome information is readily available for molecular and genetic analysis. We prepared an Hd-rR (p53(+/−), p53(−/−)) and Hd-rR HNI hybrid (p53(+/−)) fish-based xmrk model system to study the progression of pigment cells from hyperpigmentation to malignant tumors on different genetic backgrounds. In all strains examined, most of the initial hyperpigmentation occurred in the posterior region. On the Hd-rR background, mitf:xmrk-induced tumorigenesis was less frequent in p53(+/−) fish than in p53(−/−) fish. The incidence of hyperpigmentation was more frequent in Hd-rR/HNI hybrids than in Hd-rR homozygotes; however, the frequency of malignant tumors was low, which suggested the presence of a tumor suppressor in HNI genetic background fish. The effects on tumorigenesis in xmrk-transgenic immature medaka of a single 1.3 Gy irradiation was assessed by quantifying tumor progression over 4 consecutive months. The results demonstrate that irradiation has a different level of suppressive effect on the frequency of hyperpigmentation in purebred Hd-rR compared with hybrids.